Bibliotecas de museos en España: características específicas y análisis DAFO - López de Prado, Rosario (Revista General de Información y Documentación, 2003)
Libraries belonging to museums are institutions which are very little known, even to librarianship professionals. This lack of knowledge stems from the very notion and causes great difficulty in any management and improvement works which might be undertaken. Starting from the definition and origins of museum libraries an attempt is made to give an idea of what these institutions ought to be and, more importantly, to point out their purpose, their functions, and the users they serve, thus setting out a theoretical field in order to carry out plans for improvement. In addition, the analysis of their present situation enables us to set out the perspectives with which they will be faced in the immediate future.